Pengaruh Konsentrasi Lactobacillus acidophilus dan Tepung Sagu Terhadap Umur Simpan dan Sifat Sensori Tempe Kedelai - Febri Hamzah (Balitbangda Provinsi Lampung, 2014)
This study aimed to determine the concentration of Lactobacillus acidophilus and sago flour that extend shelf life and maintain the sensory properties of soy tempeh. This study used a Randomized Complete-Block Design (RBCD) with two factors and three replications. The first factor is the concentration of Lactobacillus acidophilus which consists of 3 levels (1%, 1.5% and 2%), while the second factor is the concentration of sago flour which consists of 4 levels (0%, 0.4%, 0.8% and 1,2%). The data were analyzed by analysis of variance and further trials with HSD test at 5% type αerror level. The results showed that the concentration of Lactobacillus acidophilus by 1.5% and by 0.4% sago flour extend the shelf life and maintain the sensory properties of soy tempeh. Shelf life at these concentrations is 112 hours. This shows that the addition of soy tempeh Lactobacillus acidophilus by 1.5% and sago flour by 0.4% able to increase the shelf life of soy tempeh up to 58 hours.